Dimensions of the COVID-19 pandemic: prevalence of common mental disorders in "invisible" health workers and their association with occupational stressors - Manuela Matos Maturino; Camila Carvalho de Sousa; Lusicleide Galindo da Silva Moraes; Danyella Santana Souza; Maria Yaná Guimarães Silva Freitas; Tânia Maria de Araújo (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To evaluate the association between occupational stressors and common mental disorders (CMD) among "invisible" health workers in the context of the COVID-19 pandemic. Method: Cross-sectional study including a probabilistic sample of 1,014 health workers from three municipalities in Bahia. CMDs were assessed using the SRQ-20. The Effort-Reward Imbalance (ERI) scale and the Demand-Control Model assessed occupational stressors. Descriptive, bivariate, and multiple analysis to evaluate the association between the variables of interest. Results: The global prevalence of CMD was 39.9%; it was higher among CHA/EDCA (47.2%), followed by management and surveillance staff (38.6%), technicians (35.4%), and support/maintenance/cleaning staff (29.9%). The association between occupational stressors and CMD varied among occupations: 1. Excessive work commitment (EWC), effort-reward imbalance (ERI), and psychological demand were associated with CMD among support/maintenance/cleaning workers; 2. EWC and ERI were associated with CMD among CHA/EDCA; 3. EWC, ERI, and low control over work were associated with CMD among technicians; 4. Among management and surveillance workers, only ERI remained associated with CMD. Conclusions: Occupational stressors played a relevant role in mental illness, with variation between occupational strata, demanding attention, monitoring, and control.